Reconstruction Of Audio-Visual Learning Media Based On TPACK (Pedagogical Content And Knowledge Technology) On Moral Theology Material - Putra, Ino Angga; Rahma, Yuhyil Ayda; Nisa, Khoirun; Anwar, Moh. Saiful (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This research aims to design an audio-visual learning media based on TPACK (Technological, Pedagogical, Content Knowledge) that can increase students' understanding of learning concepts in Aqidah Akhlak material and can improve the quality of learning for teachers. The method used in this research is Research and Development (R&D) research. The development model used in this research is ADDIE including Analysis, Design, Development, Implementation, and Evaluation. The research and development procedures that will be carried out by researchers only consist of three stages, namely analysis, design, and development. The limitation of this research is only at the development stage due to limited time and energy. This research was conducted on class XI students of MA Nizhamiyah Ploso and MAN 4 Jombang. The research instrument used material validation sheets, media validation and student response questionnaires. Data collection through product validation and student responses to the product. Data were analyzed using product feasibility tests and product response tests by students. The results of the research on TPACK-based audiovisual learning media on moral creed material produced obtained results after going through the revision and validation stages with an average score of 88% in material validation and media validation obtained an average score of 84%, the material expert validator and media expert stated that Learning media is very relevant and worth using. Then, at the test stage, students' responses to the suitability of the learning media obtained an average score of 83% with very interesting criteria.